King of the armadillos - Chin-Tanner, Wendy (Flatiron Books, 2023)
"A transcendent debut novel about family, love, and belonging, set against the backdrops of 1950s New York City and a historical leprosarium in Louisiana, following one young man's quest to not only survive, but live a full and vibrant life Perfect for fans of Jacqueline Woodson's Red at The Bone, Netflix's Atypical, and The Guernsey Literary and Potato Peel Pie Society. Victor Chin's life is turned upside down at the tender age of 15. Diagnosed with Hansen's disease, otherwise known as leprosy, he's forced to leave the familiar confines of his father's laundry business in the Bronx - the only home he's known since emigrating from China with his older brother - to quarantine alongside patients from all over the country at a federal institution in Carville. At first, Victor is scared not only of the disease, but of the confinement, and wants nothing more than to flee. Between treatments he dreams of escape and imagines his life as a fugitive. But soon he finds a new sense of freedom far from home - one without the pull of obligations to his family, or the laundry business, or his mother back in China. Here, in the company of an unforgettable cast of characters, Victor finds refuge in music and experiences first love, jealousy, betrayal, and even tragedy. But with the promise of a life-changing cure on the horizon, Victor's time at Carville is running out, and he has some difficult choices to make. A groundbreaking work of historical fiction, King of the Armadillos announces Wendy Chin-Tanner as an extraordinary new voice. Inspired by her father's experience as a young patient at Carville, this tender coming-of-age novel is a captivating look at a forgotten radical community and a lyrical exploration of the power of art"--